2012
DOI: 10.4251/wjgo.v4.i6.145
|View full text |Cite
|
Sign up to set email alerts
|

Serum M2-pyruvate kinase: A promising non-invasive biomarker for colorectal cancer mass screening

Abstract: Author contributions: Meng W and Zhu HH contributed equally to this work; Meng W conducted the study, data collection, management and analysis, and drafted the manuscript; Zhu HH did data correction, designed the analysis strategy and did data interpretation, co-drafted and revised the manuscript, reviewed and edited the whole manuscript; Xu ZF performed quality control on ELISA work; Cai SR performed previous screening work and collection of serum samples; Dong Q performed helpful work in previous screening; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 29 publications
1
8
0
3
Order By: Relevance
“…However, there appears to be some contention in the literature regarding its utility. Some studies on faecal M2-PK have shown a favorable sensitivity and specificity for colorectal cancer and adenoma [ 8 , 9 ] whilst other studies have shown an unfavorable sensitivity and specificity of faecal M2-PK [ 10 - 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…However, there appears to be some contention in the literature regarding its utility. Some studies on faecal M2-PK have shown a favorable sensitivity and specificity for colorectal cancer and adenoma [ 8 , 9 ] whilst other studies have shown an unfavorable sensitivity and specificity of faecal M2-PK [ 10 - 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Many reports in the literature have firmly established a link between PKM2 expression levels and various cancers, by IHC, biofluid and MS based analyses [65][66][67]. The synergy with CRC is also well documented [68][69][70], including elevated levels detected in patient faecal specimens [71,72]. Pyruvate kinase catalyzes the last step in the process of glycolysis (rate-limiting), transfer of a high-energy phosphate group from phosphoenolpyruvate (PEP) to ADP, producing ATP and pyruvate.…”
Section: Discussionmentioning
confidence: 99%
“…Диагностическая чувствительность детектирования для определения отличия больных КРР от здоровых лиц составила ∼ 98%, что согласуется с результатами исследования [17] и превышает чувствительность методов колоноскопии, исследования кала на скрытую кровь, определения раково-эмбрионального антигена, фекальной М2-ПК [18,19].…”
Section: результаты и обсуждениеunclassified